EJSO educational special issue from the TARPSWG: standard medical treatment and new options in retroperitoneal sarcoma - Kasper, Bernd; Baldi, Giacomo Giulio; Loong, Herbert Ho-Fung; Trent, Jonathan (European journal of surgical oncology, 2023)
Retroperitoneal soft tissue sarcomas mainly consist histologically of liposarcomas and leiomyosarcomas. For the liposarcoma subgroup, the local relapse rate seems to determine patients' overall prognosis. In contrast, leiomyosarcoma patients are challenged by the development of metastatic disease; therefore, effective systemic therapies are the cornerstone to improve patients’ outcome. No doubt, the limited number of active regimens currently available makes the treatment of patients with locally advanced and/or metastatic disease challenging and results in the overall poor prognosis of this population. In this European Journal of Surgical Oncology Educational Special Issue from the Transatlantic Australasian RetroPeritoneal Sarcoma Working Group (TARPSWG), we aim to summarize state-of-the-art systemic treatments for patients with retroperitoneal sarcomas with a focus on the locally advanced and metastatic disease setting including conventional standard chemotherapies as well as new innovative treatment approaches in order to identify current unmet medical needs guiding the sarcoma community to initiate appropriate translational research projects and design innovative clinical trials.